Identifying applicants suitable to a career in nursing: a value‐based approach to undergraduate selection. (22nd December 2016) - Traynor, Marian; Galanouli, Despina; Roberts, Martin; Leonard, Lawrence; Gale, Thomas
Abstract: Aims: The aim of this study was to complement existing evidence on the suitability of Multiple Mini Interviews as a potential tool for the selection of nursing candidates on to a BSc (Hons) nursing programme. Background: This study aimed to trial the Multiple Mini Interview approach to recruitment with a group of first year nursing students (already selected using traditional interviews). Design: Cross‐sectional validation study. This paper reports on the evaluation of the participants' detailed scores from the Multiple Mini Interview stations; their original interview scores and their end of year results. Methods: This study took place in March 2015. Scores from the seven Multiple Mini Interview stations were analysed to show the internal structure, reliability and generalizability of the stations. Original selection scores from interviews and in‐course assessment were correlated with the MMI scores and variation by students' age, gender and disability status was explored. Results: Reliability of the Multiple Mini Interview score was moderate (G = 0·52). The Multiple Mini Interview score provided better differentiation between more able students than did the original interview score but neither score was correlated with the module results. Multiple Mini Interview scores were positively associated with students' age but not their gender or disability status. Conclusion: The Multiple Mini Interview reported in this study offers a selection process that is based on the values and personal attributes regarded as desirable for a career in nursing and does not necessarily predict academic success. Its moderate reliability indicates the need for further improvement but it is capable of discriminating between candidates and shows little evidence of bias.